Passive voice in scientific style - Kučerová, Hana (Univerzita Pardubice, 2008)
The work focuses on the passive voice, the relation between active and passive, it explains how and when it is formed. It clarifies the conditions and constraints of the usage. The work describes the function of the passive and its frequency based on the analysis of selected texts written in scientific style.
Trpný rod v anglickém odborném stylu
Keywords: passive; active; agent; scientific style; functional sentence perspective; trpný rod; činný rod; agens; odborný styl; funkční větná perspektiva